Heat Transfer Characteristics of Modular Heat Storage Wall Solar Greenhouse Based on Active Heat Storage System - Delin Wu; Bowen Cui; Yao Zhang; Xue Wu; Zhirong Zou; Encai Bao (Applied Sciences, 2023)
The modular heat storage wall is a new type of solar greenhouse wall structure, which has the advantages of fast construction and good heat storage ability. This study provides data reference and practical value for producing modular heat storage wall in the construction of a solar greenhouse. In this paper, we used different heat storage materials to construct the modular wall. In the winter thermal environment test, soil module solar greenhouse (SG) and stone module solar greenhouse (PG) were controlled against each other in two greenhouses. The test results for 28 consecutive days (31 January 2021 9:00 to 28 February 2021 9:00) showed that both greenhouses could effectively increase the temperature in greenhouse by 10–12 °C. The average temperature of SG was 0.86 °C lower than that of PG during the daytime (09:00–17:00) and 0.44 °C higher than that of PG during the nighttime (17:00–09:00). Under typical sunny conditions, the average temperature differences between the inlet and outlet of SG in the heat storage and exothermic stage was less than that of PG, and the relative humidity difference was greater than that of PG. This indicated that SG had a better performance of heat preservation than PG and could raise the nighttime temperature rapidly. Under the condition of a typical cloudy day, the average temperature difference between the inlet and outlet was SG < PG and the relative humidity difference was SG > PG in the exothermic stage, which was consistent with the conclusion of sunny days. In the storage and exothermic stages of typical sunny days and cloudy days, the total heat exchange of SG was 464.87, 110.44 and 54.82 MJ and the total heat exchange of PG was 264.16, 61.60 and 46.89 MJ, respectively. Moreover, the heat storage and release of SG were more than that of PG in all stages. In summary, the thermal performance of the modular heat storage wall heliogreenhouse could meet the growth of tomato crop, in which the heat transfer performance of SG was optimum.